Bill Nye the science guy/ Phases of matter - Nye, Bill.; Disney Educational Productions (Elk Grove Village, IL : Disney Educational Productions, 2003)
"In Phases of Matter, Bill Nye takes viewers on a tour of a steel mill to help demonstrate that matter exists in three phases--solids, liquids, and gases"--Container.
"77A39VL00'
Liveaction film.
Not rated.
Created by Bill Nye, James McKenna, Erren Gottlieb ; writers, Melissa Gould...[et al.] ; edited by Michael Gross ; graphic design, Lou Zumek ; original music, Mike Green.
Host: Bill Nye.
Grade level: 4 and up.
Keywords: Science -- Experiments; Matter -- Composition; Spanish language materials -- Videorecordings; DVDs; Video recordings for the hearing impaired